Peeling sample for testing peeling strength and preparation method thereof

By using hot press-cured multi-layer film and mesh material layer structure in the peeling sample, the elastic deformation problem caused by the flexible metal sheet peeling before the substrate in the peeling test is solved, and more reliable peeling strength data is achieved Improved acquisition and material utilization.

CN119198245APending Publication Date: 2024-12-27BAIMTEC MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411362570.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the field of aviation transparent parts manufacturing, in the existing 90° peeling test method, when the adhesive strength between the film and the substrate is greater than the adhesive strength between the film and the flexible metal sheet, the flexible metal sheet is peeled off before the substrate, resulting in elastic deformation of the film. The data is invalid or cannot be stripped, and the effective peel strength data cannot be obtained.

Method used

Provide a peeling sample for peel strength testing, including a flexible metal sheet, a substrate and a film layer disposed between the flexible metal sheet and the substrate, the film layer is carried out by a multi-layer film and sandwiched in a multi-layer mesh material layer. Made by hot pressing and curing, ensuring that the film does not undergo tensile deformation during the peeling process.

Benefits of technology

Improve the test success rate, ensure the reliability and effectiveness of peel strength data, and reduce material loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119198245A_ABST
    Figure CN119198245A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material testing, and particularly relates to a peeling sample for peel strength testing and a preparation method thereof.The peeling sample for peel strength testing comprises a flexible metal sheet, a substrate and a film layer arranged between the flexible metal sheet and the substrate; and the film layer is prepared by hot-pressing and curing a plurality of layers of films and at least one net-shaped material layer clamped among the plurality of layers of films. The stripping sample can be used as a stripping sample in the GJB 446 90-degree stripping strength test method for adhesive (metal and metal) standard for stripping test, the film cannot be subjected to tensile deformation in the test process, the film cannot be subjected to tensile deformation even if the flexible metal sheet is stripped before the substrate in the stripping process, the test success rate is increased, and the test cost is reduced. Peel strength data is reliable, and material loss is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material testing, and in particular relates to a peeling sample for peeling strength testing and a preparation method thereof. Background Art

[0002] In the field of aviation transparent parts manufacturing, peeling performance is an important technical indicator of materials used for lamination, bonding and sealing. The 90° peel test is a common test method for testing the bonding performance between the peeled material and the substrate. When testing the 90° peeling performance of the film in the aviation field, GJB 446 "Adhesive 90° Peel Strength Test Method (Metal to Metal)" is usually used for testing. The sample structure specified in this test standard is a flexible metal sheet, a substrate and a film placed between the two.

[0003] When the existing sample structure is used for testing, if the bonding strength between the film and the substrate is greater than the bonding strength between the film and the flexible metal sheet, the flexible metal sheet will peel off before the substrate during the test, causing the film to undergo elastic deformation during the experiment, rendering the experimental data invalid or the film unable to be peeled off from the substrate, thereby making it impossible to obtain effective peel strength data.

[0004] To this end, the present invention is proposed. Summary of the invention

[0005] The main purpose of the present invention is to provide a peeling sample for peeling strength test and a preparation method thereof. The peeling sample of the present invention can be used for peeling test according to GJB 446 "Adhesive 90° Peel Strength Test Method (Metal and Metal)" standard. The film in the peeling sample will not produce tensile deformation during the experiment. Even if the flexible metal sheet is peeled off before the substrate during the peeling process, the film will not produce tensile deformation, thereby improving the success rate of the test, making the peeling strength data reliable, and reducing material loss.

[0006] In order to achieve the above objectives, the present invention provides the following technical solutions.

[0007] In a first aspect, the present invention provides a peeling sample for peeling strength testing, the peeling sample comprising a flexible metal sheet, a substrate and a film layer disposed between the flexible metal sheet and the substrate, the film layer being obtained by hot pressing and curing a plurality of films and at least one mesh material layer sandwiched between the plurality of films.

[0008] In some embodiments of the present invention, the film is selected from at least one of a polyurethane film and a PVB film.

[0009] In some embodiments of the present invention, the material of the mesh material layer is selected from 316 stainless steel.

[0010] In some embodiments of the present invention, the substrate is selected from inorganic glass.

[0011] In a second aspect, the present invention provides a method for preparing a peeling sample for peel strength testing according to the first aspect, the preparation method comprising the following steps:

[0012] A flexible metal sheet, a first film, one or more mesh material layers, a second film and a substrate are stacked layer by layer in sequence to obtain a stacked sample; the stacked sample is subjected to a hot pressing process under vacuum conditions to cure the first film, the one or more mesh material layers and the second film to form a film layer placed between the flexible metal sheet and the substrate, thereby obtaining the peeled sample.

[0013] In some embodiments of the present invention, the temperature of the hot pressing treatment is 60° C. to 140° C., and the time is 1 h to 5 h; and / or the hot pressing pressure of the hot pressing treatment is 800 KPa to 1200 KPa.

[0014] In some embodiments of the present invention, the heating rate of the hot pressing process is 1° C. / min to 3° C. / min.

[0015] In some embodiments of the present invention, in the stacked sample, the flexible metal sheet, the first film, the second film and the substrate have the same width; and / or the width of each layer of the mesh material is 4 mm to 8 mm wider than the width of the substrate.

[0016] In some embodiments of the present invention, in the stacked sample, the length of the flexible metal sheet is 10 mm to 20 mm longer than the length of the substrate; and / or the length of the first film and / or the second film is 5 mm to 15 mm longer than the length of the substrate; and / or the length of each layer of the mesh material is 5 mm to 15 mm longer than the length of the substrate.

[0017] In some embodiments of the present invention, in the stacked sample, a center line of each mesh material layer along its length direction is aligned with a center line of the flexible metal sheet along its length direction.

[0018] In some embodiments of the present invention, the mesh material layer has a thickness of ≤0.5 mm and a mesh size of 30 to 100 meshes.

[0019] In some embodiments of the present invention, the thickness of the first film is 0.3 mm to 3.0 mm; and / or the thickness of the second film is 0.5 mm to 3.0 mm.

[0020] In some embodiments of the present invention, in the stacked sample, an isolation belt is provided at one end of the substrate along its length direction; at the end opposite to the isolation belt, the ends of the flexible metal sheet, the first film, the one or more mesh material layers, the second film and the substrate are aligned.

[0021] In some embodiments of the present invention, the length of the substrate is 150 mm to 300 mm; and / or, based on the length direction of the substrate, the length of the isolation zone is 30 mm to 50 mm.

[0022] In some embodiments of the present invention, the isolation tape is selected from a high temperature resistant tape.

[0023] In some embodiments of the present invention, the preparation method further includes: using a connecting piece to tightly stack the various layer components in the stacked sample; hot pressing the tightly fixed stacked sample under vacuum conditions; and removing the connecting piece after the hot pressing treatment.

[0024] In some embodiments of the present invention, the vacuum degree of the hot pressing treatment is ≤-95KPa.

[0025] In some embodiments of the present invention, the connecting member is selected from a high temperature resistant tape.

[0026] In some embodiments of the present invention, the preparation method includes: stacking a flexible metal sheet, a first film, one or more mesh material layers, a second film and a substrate layer by layer in sequence to obtain a stacked sample; using a connecting member to tightly stack each layer of components in the stacked sample; hot pressing the tightly fixed stacked sample under vacuum conditions, and removing the connecting member after the hot pressing treatment to obtain the peeled sample.

[0027] The present invention also provides a peel strength test method, which comprises: using the peel strength test peel sample or the peel sample prepared by the preparation method to perform a peel strength test.

[0028] Compared with the prior art, the present invention achieves the following technical effects:

[0029] The peeling sample in the present invention can be used as the peeling sample in the GJB 446 "Adhesive 90° Peel Strength Test Method (Metal and Metal)" standard for peeling test. The film in the peeling sample will not produce tensile deformation during the experiment. Even if the flexible metal sheet is peeled off before the substrate during the peeling process, the film will not produce tensile deformation, thereby improving the test success rate, ensuring reliable peeling strength data, and reducing material loss.

[0030] The preparation method of the present invention is simple to operate, has strong universality, and can be promoted for use.

[0031] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. In the accompanying drawings:

[0033] Figure 1 A schematic diagram of the structure of a stacked sample according to some embodiments of the present invention;

[0034] Figure 2 The peel strength curve of the peeling sample prepared by the preparation method in Example 1 is shown in FIG.

[0035] Reference numerals

[0036] 1. Flexible metal sheet; 2. First film; 3. Mesh material layer; 4. Second film; 5. Base plate. DETAILED DESCRIPTION

[0037] The exemplary embodiments of the present invention will be described in more detail below with reference to specific embodiments. It should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0039] In the description of the embodiments of the present invention, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0040] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0041] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this document generally indicates that the associated objects before and after are in an "or" relationship.

[0042] In the description of the embodiments of the present invention, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0043] In the description of the embodiments of the present invention, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the embodiments of the present invention.

[0044] In the description of the embodiments of the present invention, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present invention can be understood according to specific circumstances.

[0045] When the existing peeling sample is used for the peeling test, if the bonding strength between the film and the substrate is greater than the bonding strength between the film and the flexible metal sheet, the flexible metal sheet will be peeled off before the substrate during the test, causing the film to undergo elastic deformation during the experiment, rendering the experimental data invalid or the film unable to be peeled off from the substrate, thereby failing to obtain effective peeling strength data.

[0046] To this end, the present invention provides a peeling sample for peeling strength test and a preparation method thereof in accordance with the GJB 446 "Adhesive 90° Peel Strength Test Method (Metal to Metal)" standard, so as to suppress the tensile deformation of the film during peeling, improve the test success rate, make the peeling strength data effective and reliable, and reduce material loss.

[0047] On the one hand, the present invention provides a peeling sample for peeling strength testing, which comprises a flexible metal sheet 1, a substrate 5 and a film layer disposed between the flexible metal sheet and the substrate, wherein the film layer is obtained by hot pressing and curing a multi-layer film and at least one mesh material layer 3 sandwiched between the multi-layer film.

[0048] The peeling sample in the present invention is prepared according to the test standard of GJB 446 "Adhesive 90° Peel Strength Test Method (Metal to Metal)", and no tensile deformation will occur in the peeling test, and the peeling strength data is valid and reliable. In some embodiments of the present invention, the film is selected from polyurethane film, PVB film and other film materials that can be used to test the peeling strength of the standard GJB 446 "Adhesive 90° Peel Strength Test Method (Metal to Metal)".

[0049] In some embodiments of the present invention, the material of the mesh material layer is selected from 316 stainless steel and the like.

[0050] In some embodiments of the present invention, the substrate is selected from inorganic glass.

[0051] Another aspect of the present invention provides a method for preparing a peeling sample for peeling strength testing. The key to the preparation method is to stack a flexible metal sheet 1, a first film 2, one or more mesh material layers 3, a second film 4 and a substrate 5 layer by layer in sequence to obtain a stacked sample. Figure 1 As shown, the laminated sample is subjected to hot pressing treatment under vacuum conditions, so that the first film 2, one or more mesh material layers 3 and the second film 4 are cured to form a film layer placed between the flexible metal sheet 1 and the substrate 5, thereby preparing a peeling sample suitable for the GJB 446 "Adhesive 90° Peel Strength Test Method (Metal to Metal)" standard. The film layer in the peeling sample prepared by the preparation method of the present invention will not produce tensile deformation during the experiment, thereby improving the success rate of the experiment and reducing material loss.

[0052] The method for preparing the peeling sample for peel strength test in the present invention is carried out according to the following steps.

[0053] (1) A first film 2 is placed on one side of the flexible metal sheet 1.

[0054] In some embodiments of the present invention, the thickness of the first film 2 is 0.3 mm to 3.0 mm. For example, the thickness of the first film 2 can be 0.3 mm, 0.38 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3.0 mm or any value satisfying the above range.

[0055] (2) One or more mesh material layers 3 are placed on the first film 2 at a side away from the flexible metal sheet 1 .

[0056] In some embodiments of the present invention, the center line of each mesh material layer 3 along its length direction is aligned with the center line of the flexible metal sheet 1 along its length direction.

[0057] In some embodiments of the present invention, the thickness of the mesh material layer 3 is ≤0.5 mm, for example, 0.1 mm to 0.5 mm. For example, the thickness of the mesh material layer 3 can be one of 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, or any value within the above range.

[0058] In some embodiments of the present invention, the mesh size of the mesh material layer 3 may be 30 to 100 meshes. For example, the mesh size may be 30 meshes, 40 meshes, 50 meshes, 60 meshes, 70 meshes, 80 meshes, 90 meshes, 100 meshes, or any value satisfying the above range.

[0059] In some embodiments of the present invention, the number of mesh material layers 3 can be 1 to 5 layers, for example, 1 layer, 2 layers, 3 layers, 4 layers, or 5 layers of mesh material layers can be set, and the setting can be selected according to actual conditions.

[0060] (3) A second film 4 is placed on the mesh material layer 3 at a layer away from the first film 2 .

[0061] In some embodiments of the present invention, the thickness of the second film 4 may be 0.5 mm to 3.0 mm. For example, the thickness of the second film 4 may be 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.25 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3.0 mm or any value satisfying the above range.

[0062] (4) A separation tape is provided at either end of the peel test substrate 5 in the longitudinal direction to prevent the film from adhering to the end of the substrate 5 in the subsequent steps.

[0063] In some embodiments of the present invention, the isolation tape may be a high temperature resistant tape, for example, the high temperature resistant tape is wound around the end of the substrate 5 .

[0064] In some embodiments of the present invention, the length of the substrate 5 can be 150 mm to 300 mm. For example, the length of the substrate 5 can be one of 150 mm, 160 mm, 170 mm, 180 mm, 190 mm, 200 mm, 210 mm, 220 mm, 230 mm, 240 mm, 250 mm, 260 mm, 270 mm, 280 mm, 290 mm, 300 mm or any value satisfying the above range.

[0065] In some embodiments of the present invention, based on the length direction of the substrate 5, the length of the isolation tape may be 30 mm to 50 mm, for example, a 30 mm to 50 mm high temperature resistant tape is wound on the substrate 5. Exemplarily, the length of the isolation tape may be one of 30 mm, 40 mm, 50 mm, or any value satisfying the above range.

[0066] (5) A substrate 5 with an isolation tape is placed on the side of the second film 4 away from the mesh material layer 3 to obtain Figure 1 Stacked samples of the structure shown.

[0067] (6) Align the ends of the flexible metal sheet 1, the first film 2, the one or more mesh material layers 3, the second film 4 and the substrate 5 opposite to the isolation tape, that is, align the ends of the stacked sample opposite to the isolation tape, and allow each layer to extend freely at the end with the isolation tape.

[0068] In some embodiments of the present invention, in the stacked sample, the flexible metal sheet 1 , the first film 2 , the second film 4 and the substrate 5 have the same width.

[0069] In some embodiments of the present invention, in the laminated sample, the width of each mesh material layer 3 is 4 mm to 8 mm wider than the width of the substrate 5. Exemplarily, the width of each mesh material layer 3 is 4 mm, 5 mm, 6 mm, 7 mm, 8 mm wider than the width of the substrate 5, or any value satisfying the above range.

[0070] In some embodiments of the present invention, in the stacked sample, the length of the flexible metal sheet 1 is 10 mm to 20 mm longer than the length of the substrate 5. Exemplarily, the length of the flexible metal sheet 1 is 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm longer than the length of the substrate 5 or any value that satisfies the above range.

[0071] In some embodiments of the present invention, in the laminated sample, the length of the first film 2 is 5 mm to 15 mm longer than the length of the substrate 5. Exemplarily, the length of the first film 2 is 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm longer than the length of the substrate 5, or any value that satisfies the above range.

[0072] In some embodiments of the present invention, in the laminated sample, the length of the second film 4 is 5 mm to 15 mm longer than the length of the substrate 5. Exemplarily, the length of the first film 2 is 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm longer than the length of the substrate 5, or any value that satisfies the above range.

[0073] In some embodiments of the present invention, in the laminated sample, the length of each mesh material layer 3 is 5 mm to 15 mm longer than the length of the substrate 5. Exemplarily, the length of each mesh material layer 3 is 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm longer than the length of the substrate 5, or any value satisfying the above range.

[0074] (7) Use connectors to tightly stack the various layers of components in the stacked sample.

[0075] In some embodiments of the present invention, the connecting member may be a high temperature resistant tape, for example, the high temperature resistant tape is used to tightly combine the above-mentioned layers of components together to prevent them from loosening in subsequent processing steps.

[0076] (8) Place the tightly stacked samples in a hot pressing bag and perform vacuum treatment.

[0077] In some embodiments of the present invention, the vacuum degree in the heat pressing bag is ≤-95KPa, which can be set according to actual conditions.

[0078] (9) The laminated sample is subjected to heat pressing treatment while maintaining the above-mentioned vacuum condition, so that the first film 2, one or more mesh material layers 3 and the second film 4 are cured to form a film layer placed between the flexible metal sheet 1 and the substrate 5.

[0079] In some embodiments of the present invention, the temperature of the hot pressing treatment can be 60°C to 140°C. Exemplarily, the temperature of the hot pressing treatment can be one of 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or any value satisfying the above range.

[0080] In some embodiments of the present invention, the heating rate of the hot pressing process may be 1°C / min to 3°C / min. For example, the heating rate may be 1°C / min, 2°C / min, 3°C / min, or any value within the above range.

[0081] In some embodiments of the present invention, the time of the hot pressing treatment may be 1 hour to 5 hours. For example, the time of the hot pressing treatment may be one of 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or any value satisfying the above range.

[0082] In some embodiments of the present invention, the hot pressing pressure of the hot pressing treatment may be 800 KPa to 1200 KPa. For example, the hot pressing pressure may be one of 800 KPa, 900 KPa, 1000 KPa, 1100 KPa, 1200 KPa or any value satisfying the above range.

[0083] (10) After the hot pressing treatment, the sample is taken out and the connecting parts are removed to obtain a peeled sample.

[0084] It is worth mentioning that, in the embodiment of the present invention, the isolation belt can be selectively removed according to actual needs.

[0085] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0086] Example 1

[0087] Disclosed is a peeling sample for peel strength testing and a method for preparing the same, see Figure 1 As shown, in Example 1, inorganic glass with a size of 200mm×20mm×8mm is used as the substrate 5; alumina with a size of 210mm×20mm×0.5mm is used as the flexible metal sheet 1; a 60-mesh 316 stainless steel mesh with a size of 205mm×25mm×0.1mm is used as the mesh material layer 3; and a polyurethane film with a size of 205mm×20mm×1mm is used as the first film 2 and the second film 4, that is, the stripped material.

[0088] The method for preparing the peeled sample in Example 1 comprises the following steps:

[0089] (1) A layer of polyurethane film is placed on alumina, and the thickness of the polyurethane film is 0.38 mm.

[0090] (2) Place three layers of 60-mesh 316 stainless steel mesh on the polyurethane film, and align the length center line of the 316 stainless steel mesh with the length center line of the alumina sheet.

[0091] (3) A layer of polyurethane film is placed on the top layer of 316 stainless steel mesh. The thickness of the polyurethane film is 1.25 mm.

[0092] (4) Wrap a high temperature resistant tape around one end of the inorganic glass. The length of the high temperature resistant tape along the length direction of the inorganic glass is 50 mm.

[0093] (5) Place inorganic glass wrapped with high temperature resistant tape on the polyurethane film.

[0094] (6) At the end of the inorganic glass that is not wrapped with the high-temperature resistant tape along the length direction, align the ends of the alumina, 316 stainless steel mesh, film, and inorganic glass, and allow the alumina, 316 stainless steel mesh, film, and inorganic glass to extend freely at the end of the inorganic glass wrapped with the high-temperature resistant tape.

[0095] (7) Use high temperature resistant tape to fix the above-mentioned components, namely, inorganic glass, alumina, 316 stainless steel mesh, and film, so that they fit closely together.

[0096] (8) Place the tightly fitted laminated samples into a hot pressing bag and evacuate them to a vacuum degree of -95 kPa.

[0097] (9) The laminated sample was subjected to hot pressing treatment under vacuum conditions, with a hot pressing temperature of 100°C, a heating rate of 3°C / min, a hot pressing time of 3 h, and a hot pressing pressure of 800 kPa.

[0098] (10) The sample after heat pressing treatment is taken out from the heat pressing bag, and the high temperature resistant tape is removed to obtain a peeled sample.

[0099] Five peeling samples were prepared in parallel according to the preparation method in Example 1. The peeling strength of the five peeling samples was tested according to the GJB 446 "Adhesive 90° Peel Strength Test Method (Metal to Metal)" standard. The test results are shown in Table 1.

[0100] Table 1 Summary of the peel strength between the polyurethane film and the inorganic glass in the peeling samples prepared in Example 1

[0101] Serial number Average peel force (N) Average peel strength (MPa) 1 508.69 25.43 2 519.37 25.97 3 538.4 26.92 4 520.07 26 5 606.6 30.33 average value 538.63 26.93

[0102] At the same time, the peel strength curves of the five peeling samples prepared according to the preparation method in Example 1 are as follows: Figure 2 Combined with Table 1 and Figure 2 It can be seen that the peeling sample prepared by the preparation method of the present invention is subjected to a peeling strength test according to GJB 446 "Adhesive 90° Peel Strength Test Method (Metal to Metal)". The film does not produce tensile deformation during peeling, the peeling force is stable, and the peeling strength data is accurate and effective.

[0103] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A peeling sample for peeling strength test, characterized in that: The peeling sample comprises a flexible metal sheet, a substrate and a film layer disposed between the flexible metal sheet and the substrate. The film layer is made by heat-pressing and curing a plurality of films and at least one mesh material layer sandwiched between the plurality of films.

2. The peeling sample for peeling strength test according to claim 1, characterized in that: The film is selected from at least one of polyurethane film and PVB film.

3. The peeling sample for peeling strength test according to claim 1 or 2, characterized in that: The material of the mesh material layer is selected from 316 stainless steel; Preferably, the substrate is selected from inorganic glass.

4. A method for preparing a peeling sample for peel strength testing according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The flexible metal sheet, the first film, one or more mesh material layers, the second film and the substrate are stacked layer by layer in sequence to obtain a stacked sample; The laminated sample is subjected to heat pressing treatment under vacuum conditions to solidify the first film, the one or more mesh material layers and the second film to form a film layer placed between the flexible metal sheet and the substrate, thereby obtaining the peeled sample.

5. The method for preparing a peeling sample for peel strength testing according to claim 4, characterized in that: The temperature of the hot pressing treatment is 60°C to 140°C, and the time is 1h to 5h; and / or the hot pressing pressure of the hot pressing treatment is 800KPa to 1200KPa; Preferably, the heating rate of the hot pressing process is 1°C / min to 3°C / min.

6. The method for preparing a peeling sample for peel strength testing according to claim 4, characterized in that: In the stacked sample, the flexible metal sheet, the first film, the second film and the substrate have the same width; and / or, The width of each mesh material layer is 4 mm to 8 mm wider than the width of the substrate.

7. The method for preparing a peeling sample for peel strength testing according to claim 4, characterized in that: In the stacked sample, the length of the flexible metal sheet is 10 mm to 20 mm longer than the length of the substrate; and / or, The length of the first film and / or the second film is 5 mm to 15 mm longer than the length of the substrate; and / or, The length of each mesh material layer is 5 mm to 15 mm longer than the length of the substrate.

8. The method for preparing a peeling sample for peel strength testing according to claim 4, characterized in that: In the stacked sample, the center line of each mesh material layer along its length direction is aligned with the center line of the flexible metal sheet in the length direction; Preferably, the thickness of the mesh material layer is ≤0.5 mm, and the mesh size is 30 to 100 meshes; Preferably, the thickness of the first film is 0.3 mm to 3.0 mm; and / or the thickness of the second film is 0.5 mm to 3.0 mm.

9. The method for preparing a peeling sample for peel strength testing according to claim 4, characterized in that: In the stacked sample, an isolation strip is provided at one end of the substrate along its length direction; At an end opposite to the isolation tape, the ends of the flexible metal sheet, the first film, the one or more mesh material layers, the second film, and the substrate are aligned; Preferably, the length of the substrate is 150 mm to 300 mm; and / or, based on the length direction of the substrate, the length of the isolation zone is 30 mm to 50 mm; Preferably, the isolation tape is selected from high temperature resistant tape.

10. The method for preparing a peeling sample for peel strength testing according to claim 4, characterized in that: The preparation method further comprises: Using a connector to tightly stack the various layers of components in the stacked sample; subjecting the tightly fixed laminated sample to a hot pressing process under vacuum conditions; and removing the connecting member after the heat pressing treatment; Preferably, the vacuum degree of the hot pressing treatment is ≤-95KPa; Preferably, the connecting member is selected from high temperature resistant tape.